Öffentlich-rechtlicher Rundfunk in der Krise - Hanno Beck; Andrea Beyer (Wirtschaftsdienst, 2013)
Diverse Skandale haben die öffentlich-rechtlichen Rundfunkanstalten in Misskredit gebracht. Dies hat erneut die Diskussion entfacht, ob der Rundfunk überhaupt in öffentlicher Hand produziert werden sollte. Die Autoren untersuchen dies aus ökonomischer Sicht, diskutieren die seit Anfang 2013 eingeführte Rundfunkabgabe und machen Vorschläge, wie Rundfunkleistungen anreizkompatibel angeboten werden können. – – The German system of public broadcasting has arrived at a crisis point: too many lightweight channels, too many soap operas and boulevard magazines, too little on culture and too much on celebrity. Wasted investments, product placements, misappropriation of funds and fraud led to public commotion over the German public broadcasting system, which is funded with more than 7 billion euros per year. Is German public broadcasting worth all this money? In view of these recent affairs, the debate on reforming public broadcasting in Germany has gained momentum; several ideas for reform are addressed in this article.
Keywords: D02; D73; L82; 330; Rundfunkpolitik; Rundfunkfinanzierung; Öffentlicher Sektor; Deutschland